SPATIAL TEMPORAL MAPPING OF VEGETATION COVER INDICES USING SENTINEL-2 MULTISPECTRAL INSTRUMENT IN UNAAHA CITY - Septianto Aldiansyah; Duwi Setiyo Wigati Ningsih; Risna (Badan Informasi Geospasial, 2024)
Vegetation cover in urban areas contributes to providing livable ecosystem services for humans. As urbanization continues to expand, vegetation cover in urban areas will change rapidly. This research aims to monitor changes in vegetation cover in the last 5 years in Unaaha City using Google Earth Engine. This study also explores vegetation index algorithms such as NDVI, EVI, SAVI, and MSARVI. The research results show that forest vegetation cover continues to decline, followed by an increase in built-up land with an average change of 1,021 ha or the equivalent of 55% of the total area. This research also found that the NDVI algorithm had the best average accuracy with a value of OA=82.54%, followed by MSARVI=73.23%, SAVI=69.52%, and EVI=63.62%. This makes the NDVI method have good accuracy requirements for identifying vegetation compared to other vegetation index algorithms.